(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Haryana Urban Development Authority in public quarter and licenced colonizers in private area thru Town and Country Planning Department have also performed high position in accomplishing planned development in Gurgaon - Manesar Urban Complex. The Haryana Urban Development Authority and the licenced colonizers collectively have advanced approximately 8000 hectares land for residential, industrial, institutional and industrial functions to fulfill the growing demand of the general public. The regions of Gurgaon-Manesar Urban Complex that have so far been developed in public and private region such as current city and village abadies would accommodate 22 lacs populace. In order to cater to the destiny call for of Gurgaon-Manesar Urban Complex a further location of 22957 hectares has been brought inside the shape of urbanisable vicinity for the stated complex to deal with 20.50 lacs additional populace. Thus, the whole urban sable region of Gurgaon- Manesar Urban Complex could accommodate forty two.50 lacs population by 2031 AD.